The butterfly - Polacco, Patricia (New York : Philomel Books, 2000)
During the Nazi occupation of France, Monique's mother hides a Jewish family in her basement and tries to help them escape to freedom.
School Library Journal starred
Book Links (A.L.A.)
Publisher's Weekly
4.6
K-3
Keywords: Jews -- France -- Juvenile fiction; World War, 1939-1945 -- France -- Juvenile fiction; France -- History -- German occupation, 1940-1945 -- Juvenile fiction; Jews -- France -- Fiction; World War, 1939-1945 -- France -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; Jews -- France -- Fiction; World War, 1939-1945 -- Fiction; France -- History -- 1940-1945, German occupation. -- Fiction